International manufacturing strategy in a time of great flux - Brennan, Louis; Vecchi, Alessandra (Springer, 2017)
This book assesses the state of international manufacturing strategy and clarifies how recent developments, for example regarding configuration, technology, and the environment, are impacting on its content and direction and on its relationship to manufacturing performance. In providing up-to-date coverage of the consequences of such forces and factors for international manufacturing, this book aims to expand the debate concerning international manufacturing strategy and cast light on its current evolution. International manufacturing is operating within a time of great flux. While offshoring of activities has dominated over recent decades, nearshoring and reshoring are increasingly being considered and observed in practice. At the same time, technologies such as 3D-printing are gaining traction and the role of ICT and data analytics is increasingly important in the international manufacturing landscape while digitization becomes more prevalent and the embrace of the Internet of Things (IOT) accelerates. Furthermore, issues related to the environment are figuring more prominently in international manufacturing considerations, and assumptions regarding the long-term cost of energy are being called into question. International manufacturing is also experiencing greater servitization.
Keywords: Production planning.; Production management.; Competition.; Manufacturing industries.; elektronické knihy; electronic books